2016
DOI: 10.21162/pakjas/16.3970
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agricultural Services Provided by Non-State Actors on Rural Livelihoods: A Case of District Mansehra, Khyber Pukhtunkhwa, Pakistan

Abstract: The failure of state actors/institutions in the country in delivering agricultural advisory and extension services to the rural community created a space for non-state actors to deliver these services at the door steps of majority of the rural poor people in order to improve their livelihoods. This situation prevails in all the four provinces of the country especially in Khyber Pakhtunkhwa province, where rural poverty is evident. In order to access the impact of agricultural services rendered by different non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 6 publications
4
9
1
Order By: Relevance
“…Likewise, Akintonde et al (2012) concluded that T&V system provided an organizational structure and comprehensive delivery medium by ensuring the regular visit of extension field workers and transferring information relevant to farmers' needs and problems. These findings are contradictory to those of Luqman et al (2016) who reported that non-state actors played effective role in dissemination of information as compared to state actors. Moreover, agricultural services were successfully rendered by private sector in the study area.…”
Section: Resultscontrasting
confidence: 99%
“…Likewise, Akintonde et al (2012) concluded that T&V system provided an organizational structure and comprehensive delivery medium by ensuring the regular visit of extension field workers and transferring information relevant to farmers' needs and problems. These findings are contradictory to those of Luqman et al (2016) who reported that non-state actors played effective role in dissemination of information as compared to state actors. Moreover, agricultural services were successfully rendered by private sector in the study area.…”
Section: Resultscontrasting
confidence: 99%
“…Non-state institutions were providing relief to people (84%) in terms of technical guidance and monetary services and improving rural infrastructure (80%). Findings are similar to those of Luqman et al (2016) where they found non-state actors achieving their objectives, increasing farm production, improving livelihood, achieving food security, and escalating social capital within society in KPK. N. Ahmad et al (2009) and Zada et al (2019) have concluded that non-state actors boosted the self-confidence and vision of self-help among people in KPK through learning-centered training sessions with people in the region.…”
Section: Which Type Of Rural Development Actor Is Playing Significant Role In Reducing Rural Poverty Through Different Rural Development-supporting
confidence: 71%
“…The staff has an effective approach to utilize their strength to meet their goals. Bhaskar and Geethakutty (2001) had appraised the contribution of non-state institutions toward sustainable development and alleviation of poverty through poverty alleviation programs under NGOs (Enyioko, 2012) and Civil Society Organizations (CSOs) (Luqman et al, 2016). One of the key informants discussed different reasons persuading people to acclaim non-state institutions and commented about the extension advisory service providers in particular:…”
Section: Comparative Effectiveness Of State and Non-state Actors With Regard To Different Rural Development Servicesmentioning
confidence: 99%
See 2 more Smart Citations